British Association for Sexual Health and HIV national guideline for the management of infection with Mycoplasma genitalium (2018). (September 2019) - Soni, Suneeta; Horner, Paddy; Rayment, Michael; Pinto-Sander, Nicolas; Naous, Nadia; Parkhouse, Andy; Bancroft, Darren; Patterson, Carl; Fifer, Helen
This is the first British Association for Sexual Health and HIV (BASHH) guideline for the diagnosis and management of Mycoplasma genitalium in people aged 16 years and older. The guideline is primarily aimed at level 3 sexually transmitted infection (STI) management services within the UK, although it could also serve as a reference guide for STI services at other levels.